Search for flavour-changing neutral current top-quark decays $t→ qZ$ in proton-proton collisions at $\sqrt{s}=13$ TeV with the ATLAS detector - ATLAS collaboration (2869 authors) (2018)
A search for flavour-changing neutral-current processes in top-quark decays is presented. Data collected with the ATLAS detector from proton-proton collisions at the Large Hadron Collider at a centre-of-mass energy of $\sqrt{s}=13$ TeV, corresponding to an integrated luminosity of 36.1 fb$^{-1}$, are analysed. The search is performed using top-quark pair events, with one top quark decaying through the $t→ qZ$ $(q = u, c)$ flavour-changing neutral-current channel, and the other through the dominant Standard Model mode $t→ bW$. Only $Z$ boson decays into charged leptons and leptonic $W$ boson decays are considered as signal. Consequently, the final-state topology is characterized by the presence of three isolated charged leptons (electrons or muons) and at least two jets, one of the jets originating from a $b$-quark. The data are consistent with Standard Model background contributions, and at 95% confidence level the search sets observed (expected) upper limits of $1.7×10^{-4}$ ($2.4×10^{-4}$) on the $t→ uZ$ branching ratio and $2.4×10^{-4}$ ($3.2×10^{-4}$) on the $t→ cZ$ branching ratio, constituting the most stringent limits to date.